Microvesicles of pregnant women receiving low molecular weight heparin improve trophoblast function. (January 2016) - Shomer, Einat; Katzenell, Sarah; Zipori, Yaniv; Rebibo-Sabbah, Annie; Brenner, Benjamin; Aharon, Anat
Abstract: Introduction: Microvesicles including exosomes and microparticles, participate in the placental-maternal crosstalk in normal pregnancies and gestational vascular complications (GVC). Low molecular weight heparin (LMWH) is known to reduce the risk of placenta-mediated pregnancy complications. This study was aimed to characterize microvesicles of pregnant women receiving LMWH and explore microvesicle involvement in trophoblast and endothelial cell function. Materials and methods: Microvesicles were isolated from blood samples obtained from non-pregnant women, healthy pregnant women (HP) and pregnant woman treated with LMWH. Microvesicle protein contents were assessed by protein array and ELISA. Microvesicle effects on early stage trophoblasts, term trophoblasts and endothelial cell migration, angiogenesis and apoptosis were evaluated. Results: Microvesicles derived from the group treated with LMWH contained higher levels of several proangiogenic proteins compared to those of HP women. Exposure of endothelial cells to circulating microvesicles derived from HP and LMWH treated groups induced significantly higher cell migration and branch tube formation compared to untreated cells. The effect of microvesicles from HP- and LMWH groups on early-stage trophoblast migration was similar. Microvesicles derived from these two study groups significantly decreased early-stage trophoblast apoptosis, while microvesicles derived from the HP-group (but not from the LMWH-group) significantly increased the term trophoblast apoptosis (TUNEL assay) compared to untreated cells. Conclusion: Therapy with LMWH affects patients' microvesicle content, leading to normalization of invasion, angiogenesis activity and survival of endothelial and trophoblast cells in vitro. The effects of LMWH on microvesicles may point to an additional mechanism of heparin action in high-risk pregnancy. Highlights: Low molecular weight heparin (LMWH) treatment affects patients' microvesicle (MV) content MVs of healthy pregnant women (HP) and pregnant women on LMWH induced higher endothelial cell migration than untreated cells MVs of HP women and pregnant women on LMWH induced higher tube formation than untreated cells MVs derived from HP and LMWH groups significantly decreased early-stage trophoblast apoptosis MVs derived from the HP-group (but not from the LMWH-group) significantly increased the term trophoblast apoptosis